2006
DOI: 10.1111/j.0023-8333.2006.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

How Do English L1 Learners of Advanced Japanese Infer Unknown Kanji Words in Authentic Texts?

Abstract: This study investigates advanced Japanese language learners' abilities to infer unknown kanji (Chinese character) words while reading authentic Japanese texts. Data obtained from 42 English L1 students indicate that, first, although they can guess the meanings of unknown kanji words in context, they frequently make erroneous guesses or fail to guess at all. Second, the more proficient students can use context better than the less proficient students. Third, when reading comprehension ability is controlled, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 34 publications
(62 reference statements)
1
25
2
2
Order By: Relevance
“…How DGBLL can be deployed both in and outside of the classroom to teach specific linguistic features in L2 development may be of interest to future L2 researchers. Further, the Japanese writing system presents a special challenge to students, as its orthographic systems are difficult to master for many learners (e.g., Kondo-Brown, 2006). How effectively DGBLL can be employed to overcome this challenge would be an interesting and pertinent research area in Japanese language research.…”
Section: Future Implicationsmentioning
confidence: 99%
“…How DGBLL can be deployed both in and outside of the classroom to teach specific linguistic features in L2 development may be of interest to future L2 researchers. Further, the Japanese writing system presents a special challenge to students, as its orthographic systems are difficult to master for many learners (e.g., Kondo-Brown, 2006). How effectively DGBLL can be employed to overcome this challenge would be an interesting and pertinent research area in Japanese language research.…”
Section: Future Implicationsmentioning
confidence: 99%
“…Other studies have consistently demonstrated that the use of multiple sources of information leads to better learning than reliance on a single source of information (Mori, , ; Shen, ). Available strategies include compositional analysis (Jackson, Everson, & Ke, ; Kubota & Toyoda, ; Mori, ; Mori et al, ; Shen & Ke, , Toyoda, ; Yamashita & Maru, ), context‐based strategies (Kondo‐Brown, ; Mori, , Mori & Nagy, ; Taniuchi & Komori, ; Yamagata, ), mnemonic strategies (Kuo & Hooper, ; Kuwabara, ; Rose, ; Soemer & Schwan, ; Toyoda & McNamara, ; Verhaeghen, Palfai, & Johnson, ), and repeated writing (Butler, ; Gamage, , Nesbitt, ; Thomas, , ; Winke, ). The pedagogical implication is that L2 students should be encouraged to use multiple strategies flexibly and effectively in an enriched, multimodal learning environment, as the ability to use metacognitive strategies can be improved through strategy instruction (Ulambayar, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, issues in L2 kanji include kanji learning/teaching strategies (Shimizu & Green, 2002;, memory and retrieval (Chikamatsu 2005), radical/compositional awareness (Toyoda 2000;Yamashita & Maru 2000;Kubota & Toyoda 2001;Mori, Sato & Shimizu 2007), the role of contextual and morphological information in interpreting novel kanji words (Y. Mori , 2003Kondo-Brown 2006a;, the transferability of L1 knowledge among learners with Chinese-character backgrounds (Kato 2005;Sawabe & Yasui 2008), the role of teacher feedback in learning to write kanji characters (Kubota 2005), and teacher/student perceptions of kanji teaching/learning (Y. Shimizu & Green 2002;Gamage 2003;Grainger 2005;.…”
Section: Vocabulary and Kanji Learningmentioning
confidence: 99%
“…Similarly, L2 students are able to use information from component characters to infer the meanings of novel kanji compounds (Y. Mori , 2003aKondo-Brown 2006a;.…”
Section: Vocabulary and Kanji Learningmentioning
confidence: 99%
See 1 more Smart Citation